2015
DOI: 10.1016/j.gca.2015.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Ge/Si and Ge isotope ratios as geochemical tracers of seafloor hydrothermal systems: Case studies at Loihi Seamount and East Pacific Rise 9°50′N

Abstract: International audienceGermanium (Ge) and Silicon (Si) exhibit similar geochemical behavior in marine environments but are variably enriched in seafloor hydrothermal fluids relative to seawater. In this study, Ge isotope and Ge/Si ratio systematics were investigated in low temperature hydrothermal vents from Loihi Seamount (Pacific Ocean, 18°54′N, 155°15′W) and results were compared to high-temperature vents from the East Pacific Rise (EPR) at 9°50′N. Loihi offers the opportunity to understand contrasting Ge an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
86
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(97 citation statements)
references
References 77 publications
(190 reference statements)
10
86
1
Order By: Relevance
“…Recently Baronas et al (2016) have suggested that Ge loss from the ocean appears to be dependent on pore-water oxidation-reduction reactions and the formation authigenic aluminosilicate (see section Sedimentary Processes) minerals within marine sediments. Note, a recent study looking at the links between Ge isotopes and silicon in Hawaiian hydrothermal vents has shown the potential of this new isotopic system to trace the fate of hydrothermal elements released into the ocean (Escoube et al, 2015).…”
Section: Germaniummentioning
confidence: 99%
“…Recently Baronas et al (2016) have suggested that Ge loss from the ocean appears to be dependent on pore-water oxidation-reduction reactions and the formation authigenic aluminosilicate (see section Sedimentary Processes) minerals within marine sediments. Note, a recent study looking at the links between Ge isotopes and silicon in Hawaiian hydrothermal vents has shown the potential of this new isotopic system to trace the fate of hydrothermal elements released into the ocean (Escoube et al, 2015).…”
Section: Germaniummentioning
confidence: 99%
“…Evidence for modest fractionation during evolution of hydrothermal fluids Ge [134] and references therein, [135] Ge concentrated in sphalerite; potential for tracing processes in seafloor hydrothermal systems.…”
Section: Non-traditional Stable Isotopesmentioning
confidence: 99%
“…Experimental study also demonstrates that Ge is likely to be absorpted by or coprecipitated with iron hydroxides and organo-mineral colloids in many superficial aquatic environments at the contact of anoxic groundwaters with surficial oxygenated solutions (Pokrovsky et al, 2006). Some studies also conclude that "missing Ge sink" in ocean is due to Ge sequestration into authigenic Fe-oxyhydroxides in marine sediments (Escoube et al, 2015). However, Ge/Si ratios of iron formations indicate that silica is dominantly derived from weathering of continental landmass, whereas iron has a hydrothermal origin (Hamade et al, 2003).…”
Section: Ge Enrichment In Magnetite Of Iron Formationsmentioning
confidence: 91%
“…Inorganic Ge exists as the same chemical species as Si in natural waters due to their similar atomic radii and Si-O, Ge-O bond lengths and can substitutes for Si in the SiO 2 lattice (Pokrovski and Schott, 1998). Ge/Si ratios have been used to discuss the genesis of banded iron formations because the Ge/Si ratio preserved in iron formation silica should reflect the ratio of the water from which it precipitated and hence reflect its source (e.g., Hamade et al, 2003;Delvigne et al, 2012;Escoube et al, 2015). Previous studies mainly focus on the Ge/Si ratios of Fe-rich layers and Si-rich layers such as chert.…”
Section: Ge/si Ratio Of Magnetite As a Geochemical Tracermentioning
confidence: 99%